PERAN KELOMPOK TANI DALAM UPAYA MENINGKATKAN PRODUKTIVITAS USAHATANI PADI SAWAH TADAH HUJAN DI DESA KEISIO KECAMATAN LALOLAE KABUPATEN KOLAKA TIMUR - Febriana, Isra; Rianse, Usman; Rosmawaty, Rosmawaty (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
This study aims to determine the role of farmer groups and the level of productivity of rainfed wetland rice farming in Keisio Village and to determine the relationship between the role of farmer groups in efforts to increase the productivity of rainfed wetland rice farming in Keisio Village, Lalolae District, East Kolaka Regency. Determination of the location is done intentionally (Purposive) with several considerations, namely Keisio Village is one of the villages with the majority of people working as rainfed wetland rice farmers, and is also the one that has rice fields with an area of approximately 300 hectares. The population in this study were all farmers who were members of farmer groups, namely 225 people, with a research sample of 34 people. The results showed that the role of farmer groups in increasing the productivity of paddy rice farming in Keisio Village, Lalolae Subdistrict, East Kolaka Regency went well as seen from the role of farmer groups as a learning class in the high category (67.64%), as a vehicle for cooperation in the high category (70.58%), and only as a production unit in the medium category (70.58%). The productivity of wet-rice farmers in Keisio Village in 2022 can be said to be high, namely 4.73 tons/ha. The role of farmer groups on the productivity of paddy rice farming has a close relationship with a correlation coefficient value of 0.780 with a significant level of 0.000. So that the better the role of farmer groups, the better the productivity level of paddy rice farming.